TERAPI SENAM KAKI DIABETIK POSISI BERBARING TERHADAP PERUBAHAN KADAR GULA DARAH PADA LANSIA PENDERITA DIABETES MELLITUS TIPE 2 DI DESA PAGU KABUPATEN KEDIRI - dwi setyorini; Mersa Monica Ayu Takke Permatasari; Moch. Maftuchul Huda (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Type 2 diabetes mellitus is up to normal metabolic inside the body have been marked by the increased blood sugar rate and involved decreasing body function, hence the effort of decreasing blood sugar rate is needed by diabetic foot exercises therapy. The research aims to find out the influence of diabetic food exercise therapy with lie down position on the changeover blood glucose rate at aged who have suffered type 2 diabetes mellitus in Pagu Village Kediri Regency. The research used a “quasi-experimental study” with data collection techniques of purposive sampling, and the glucometer instrument auto-check brand that gained 32 respondents. The result of the study showed that almost all of the respondents before the intervention of diabetic foot exercises therapy with lie down position had a worn-out blood glucose rate and after the intervention of diabetic foot exercises therapy with lie down position most of the respondents had an average blood glucose rate. Meanwhile, the control group without pre-post intervention showed that whole respondents had a bad blood glucose rate. The analysis Wilcoxon test obtained a p-value of 0.000 < 0.05 there was an effect of lying position diabetic foot exercise therapy in the intervention group, while the Wilcoxon test obtained a p-value of 1,000 > 0.05 there was no effect of diabetic foot exercise therapy lying down in the control group and test used Mann-Whitney and obtained a p-value 0,000 < α 0.05. So there was the influence of diabetic food exercise therapy with lie down position toward the change over blood glucose rate at ages who have suffered the type 2 diabetes mellitus in Pagu Village Kediri Regency. Diabetic foot exercise therapy can increase transcription of GLUT4 mRNA in the lower extremity area (legs) which functions to activate insulin receptors so that blood sugar levels in the body decrease. In conclusion, it’s suggested to the type 2 diabetes mellitus sufferer do diabetic foot exercises therapy to support the decreasing of blood sugar rate